2021
DOI: 10.1016/j.ajpath.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Hyaluronan Accumulation/Depolymerization in Osteoarthritic Joints

Abstract: In healthy articular cartilage, the extracellular matrix (ECM) is properly maintained by the overall anabolic and catabolic balance of slow synthesis and degradation, a so-called homeostatic state, under the influence of synovial metabolism. Though the ECM of articular cartilage tissue contains low amounts of hyaluronan (HA), its main components are collagen, type II, IX, and XI, and proteoglycans, such as aggrecan. Nevertheless, HA plays crucial roles in cartilage, especially in retaining aggrecan in tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Differential roles of HYBID and TMEM2 in normal and OA cartilage remain to be clarified. However, our recent study on the experimental knee OA models using Hybid-deficient mice demonstrated that cartilage destruction and osteophyte formation are suppressed in Hybid-deficient mice and suggested that Hybid plays a key role in the progression of mechanically induced knee OA by HA degradation in joint tissues including the articular cartilage and synovium 22 , and could be a potential therapeutic target on the onset of OA 23 . In addition, a very recent study by Deroyer et al reported that HYBID (CEMIP, KIAA1199) overexpressed by OA synovial tissue is implicated for synovial inflammation and hyperplasia 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Differential roles of HYBID and TMEM2 in normal and OA cartilage remain to be clarified. However, our recent study on the experimental knee OA models using Hybid-deficient mice demonstrated that cartilage destruction and osteophyte formation are suppressed in Hybid-deficient mice and suggested that Hybid plays a key role in the progression of mechanically induced knee OA by HA degradation in joint tissues including the articular cartilage and synovium 22 , and could be a potential therapeutic target on the onset of OA 23 . In addition, a very recent study by Deroyer et al reported that HYBID (CEMIP, KIAA1199) overexpressed by OA synovial tissue is implicated for synovial inflammation and hyperplasia 24 .…”
Section: Discussionmentioning
confidence: 99%